MULTIVOXEL MAGNETIC RESONANCE SPECTROSCOPY IN THE DIAGNOSIS OF BRAIN TUMORS - Bakhritdinov B.R; Aliev M.A; Mardieva G.M (Scholar Express Journals, 2022)
To study the possibilities of multivoxel magnetic resonance spectroscopy (MRS), patients with brain tumors were examined. Verification of the tumor was carried out by histological examination of the surgical material. Hydrogen MR spectroscopy revealed significant differences in the content of metabolites between tumor types. Compared to tumors of the neuroectodermal tissue, tumors of the meningovascular series were characterized by minimal values of the proportion of N-acetylaspartate and the presence of alanine metabolite. Glial tumors were characterized by intermediate values of the shares of Nacetylaspartate, creatine, as well as the absence of alanine content. The use of MRS is advisable not only for the purpose of differential diagnosis of various types of tumors, but also in situations where the data of conventional MRI do not correspond to the obtained clinical manifestations, as well as to clarify the degree of anaplasia of glial tumors.
Keywords: Magnetic resonance spectroscopy; brain; glial tumors; meningiomas